Psycheducation Affecting Family Psychomotor in Treatment of the Scizofrenia Client - Hardiyati Hardiyati; Zulhaini Sartika A. Pulungan; Masnaeni Ahmad (Universitas Muhammadiyah Semarang, 2020)
Psychosis, including schizophrenia, is the most common serious mental illness affecting 1% of the population worldwide. Family support is the most important part of the schizophrenia patient care process. Family support and motivation is very useful in care and treatment. Psychoeducation is a way of providing information and education through therapeutic communication. The purpose of this study was to determine the effect of psychoeducation on improving family psychomotor and schizophrenic clients in Mamuju district. This research is a pre-experimental study with a pre-post test design without a control group design, where one-group pretest-posttest design is designed. The population in this study were caregivers who have family members with mental disorders in the working area of Puskesmas Tampa Padang, West Sulawesi. The sample was obtained by purposive sampling totaling 23 families. The data were collected in two periods where pre-test and post-test were carried out before the intervention after the implementation of family psychoeducation, five sessions of 45 minutes each. The data were analyzed using paired t-test to determine the cognitive abilities of the family before and after psychoeducation. The results showed that there was an increase in family psychomotor abilities after being given psychoeducation with a value of p = 0.000. The conclusion is that psychoeducation in families improves family psychomotor in caring for schizophrenic clients.